IgE and TGF-β Signaling: From Immune to Cardiac Remodeling - Cao H (Dove Medical Press, 2021)
Hua Cao,1 Chungang Xiao,1 Zhangxiu He,2 Hong Huang,3,4 Huifang Tang1,4 1The First Affiliated Hospital, Department of Cardiology, Hengyang Medical School, University of South China, Hengyang, Hunan, 421001, People’s Republic of China; 2The First Affiliated Hospital, Department of Nephrology, Hengyang Medical School, University of South China, Hengyang, Hunan, 421001, People’s Republic of China; 3The First Affiliated Hospital, Institute of Clinical Medicine, Hengyang Medical School, University of South China, Hengyang, Hunan, 421001, People’s Republic of China; 4The First Affiliated Hospital, Institute of Cardiovascular Disease, Hengyang Medical School, University of South China, Hengyang, Hunan, 421001, People’s Republic of ChinaCorrespondence: Hong Huang; Huifang TangThe First Affiliated Hospital, Institute of Cardiovascular Disease, Hengyang Medical School, University of South China, Hengyang, Hunan, 421001, People’s Republic of ChinaEmail trave1@126.com; tanghuifang999@163.comAbstract: Cardiac remodeling is accompanied by cardiac hypertrophy, fibrosis, and dysfunction, eventually leading to heart failure (HF). However, the molecular mechanisms involved in cardiac remodeling are complicated, especially the association with immune. Immunoglobulin E (IgE) is a class of immunoglobulins involved in immune response to specific allergens. Recently, Zhao et al characterized a novel specific role of IgE and its high affinity receptor (FcϵR1) in directly promoting pathological myocardial remodeling and cardiac dysfunction. Additionally, upon blocking IgE-FcϵR1 signaling using FcϵR1 genetic depletion or by administrating the anti-IgE monoclonal antibody omalizumab (Oma) in mice, they observed that cardiac hypertrophy and cardiac interstitial fibrosis induced by angiotensin II (Ang II) or transverse aortic constriction (TAC) were significantly suppressed. In contrast, IgE administration alone can aggravate pathological cardiac remodeling and dysfunction. RNA-seq and downstream analysis indicated that TGF-β was the common pathway and the most pivotal mediator in IgE-FcϵR1-induced cardiac remodeling and dysfunction. Furthermore, the administration of a TGF-β inhibitor could ameliorate cardiac remodeling and improve cardiac function. Therefore, these findings suggest that IgE-FcϵR1 maybe promising therapeutic targets for cardiac remodeling and provide an experimental basis for the use of omalizumab for HF patients combined with high serum IgE levels or allergic diseases.Keywords: cardiac remodeling, IgE- FcϵR1, immunoglobulins, TGF-&#x03B2